Preeclampsia: From Cellular Wellness to Inappropriate Cell Death, and the Roles of Nutrition - Lokeswara, Angga Wiratama; Hiksas, Rabbania; Irwinda, Rima; Wibowo, Noroyono (Frontiers in Cell and Developmental Biology, 2021)
In preeclampsia, alterations of plasma membrane, mitochondrial dysfunction, endoplasmic reticulum stress, and changes in gene expression, DNA methylation, and miRNA expression, as well as weakened defence against environmental contaminants may induce a series of inappropriate cellular deaths such as abnormal apoptosis and necrosis, and autophagy dysfunction and resulting in abnormal trophoblast invasion. Despite their inherent connection, the currently available studies examined the functions of each organelle, the cellular death mechanisms and the nutrition involved, both physiologically in the placenta and in preeclampsia, separately. Therefore, this review aims to comprehensively discuss the relationship between each organelle in maintaining the physiological cell death mechanisms and the nutrition involved, and the interconnection between the disruptions in the cellular organelles and inappropriate cell death mechanisms, resulting in poor trophoblast invasion and differentiation, as seen in preeclampsia.